Co-creating strategy between independent consultants in a micro-firm context - Tanja Lepistö; Satu Aaltonen; Ulla Hytti (Edward Elgar Publishing, 2022)
Today, value creation is not solely in the hands of a single service provider but instead usually involves networks of other companies, such as suppliers or retailers. The current business environment has amplified the need to consider not only how to address consumer needs more perceptively but also how partners can be incorporated into the practice of creating value propositions. Thus, success relies on building a strategy capable of integrating this networked way of doing business that involves interaction, and collaboration. This chapter directs attention to the co-creation between partners in a micro firm context. Five dialoguing practices occursing in the strategy co-creation workshops were identified: dialoguing about the customer, about who we are and and what we do, dialoguing the utilization of a rabnge of varied experience and knowledge in customer co-operation, dialoguing the required steps regarding the future and, dialoguing the need for a customer perspective. According to our study, the way in which the strategy was evolving in the dialogue could be viewed as an outcome of social construction. The findings also indicate co-strategizing in micro firms is an iterative and ongoing process that needs time and space to develop in the midst of business as usual. The practical importance of this analysis lies in providing insights for firms in relation to why and how co-strategizing can prove beneficial. Perhaps the most important aspect for the future of small firms is the determination of tangible steps and activities to advance strategy implementation and the awareness that such steps can be small and involve experimentation if appropriate.
The Dynamics of Entrepreneurial Contexts